(untitled) (Journal of Geography and Environmental Management, 2019)
In article are considered strengthening of processes èkzomorfogenez in connection with an aridizatsiya of climate and an ekologogeomorphological situation in the conditions of the industrial Zhezkazgan-Ulytau region of the Central Kazakhstan.